(untitled) (MAUSAM, 2001)
Visibility plays a key role at the time of landing and take off operations at airports. The daily visibility data from 1969 onwards for 25 stations in the country (at 2100, 0000, 0300 and 0600 UTC) are examined for the winter period. Side by side the dry bulb temperatures and the relative humidity recorded at the same time are also examined. Linear trend regressions have been fitted on the data sets for each of the cities. The significance is tested at 99% level of confidence. In recent years, degradation of air quality in the cities has often been suggested as the cause for the increase in the number of poor visibility days <2000 meters) particularly in the morning hours. Continuous persistence of this phenomenon for a number of days has also been reported. The results show that there are decreasing trends in visibility at most of the stations. At 0300 UTC the visibility is generally low and increased afterwards due to mixing and turbulence in the boundary layer.